Intestinal permeability in Behçet's syndrome. Issue 1 (1st January 2001) - Fresko, I; Hamuryudan, V; Demir, M; Hızlı, N; Sayman, H; Melikoğlu, M; Tunç, R; Yurdakul, S; Yazıcı, H
Abstract : OBJECTIVE: To measure the intestinal permeability in patients with Behçet's syndrome (BS) and to compare the results with those obtained from healthy and diseased controls. METHOD: The study group comprised 34 patients with BS without known gastrointestinal disease. Ten patients with ankylosing spondylitis (AS), 6 with inflammatory bowel diseases (IBD), 17 with systemic lupus erythematosus (SLE), and 15 healthy subjects (HC) constituted the controls. All patients received 100 μCi (3.7 MBq) of chromium-51 EDTA ( 51 Cr-EDTA) as a radioactive tracer after a 72 hour abstinence from all drugs. The percentage of the isotope excreted in a 24 hour urinary specimen was the measure of permeability. RESULTS: The percentage (SD) rate of excretion of 51 Cr-EDTA was 4.6 (2.6) in BS, 6 (2.4) in AS, 5.2 (1.9) in IBD, 5.56 (1.78) in SLE, and 2.3 (1) in healthy controls. (Analysis of variance: f=6.4, p=0.0002. BS v HC, AS v HC, SLE v HC significant.) CONCLUSION: The intestinal permeability in BS was significantly more than that seen among the healthy controls. Similar results in all the diseased controls cast doubt on its specificity.